Different Preclimacteric Events in Apple Cultivars with Modified Ripening Physiology - Singh, Vikram; Weksler, Asya; Friedman, Haya (Frontiers in Plant Science, 2017)
‘Anna’ is an early season apple cultivar exhibiting a fast softening and juiciness loss during storage, in comparison to two mid-late season cultivars ‘Galaxy’ and ‘GD’. The poor storage capacity of ‘Anna’ was correlated with high lipid oxidation-related autoluminescence, high respiration and ethylene production rates, associated with high expression of MdACO1, 2, 4, 7 and MdACS1. All cultivars at harvest responded to exogenous ethylene by enhancing ethylene production, typical of system-II. The contribution of pre-climacteric events to the poor storage capacity of ‘Anna’ was examined by comparing respiration and ethylene production rates, response to exogenous ethylene, expression of genes responsible for ethylene biosynthesis and response, and developmental regulators in the three cultivars throughout fruit development. In contrast to the ‘Galaxy’ and ‘GD’, ‘Anna’ showed higher ethylene production and respiration rates during fruit development, and exhibited auto-stimulatory (system II-like) effect in response to exogenous ethylene. The higher ethylene production rate in ‘Anna’ was correlated with higher expression of ethylene biosynthesis genes, MdACS3a, MdACO2, 4 and 7 during early fruit development. The expression of negative regulators of ripening (AP2/ERF) and ethylene response pathway, (MdETR1,2 and MdCTR1) was lower in ‘Anna’ in comparison to the other two cultivars throughout development and ripening. Similar pattern of gene expression was found for SQUAMOSA promoter binding protein (SBP)-box genes, including MdCNR and for MdFUL. Taken together, this study provides new understanding on pre-climacteric events in ‘Anna’ that might affect its ripening behaviour and physiology following storage.